Molecular phylogenetics, taxonomy and niche-based conservation risk assessment of Thesium L. (Santalaceae) - Zhigila, Daniel Andrawus (Department of Biological Sciences, 2021)
Thesium L. (Santalales: Santalaceae) is a large (360 species) genus of hemiparasitic perennial or annual species with a mainly Old-World distribution and a greatest concentration in southern Africa (ca. 186 species). Although Thesium is a major component of southern African flora, it often goes unnoticed and is poorly studied. The last revision of the entire genus was done by De Candolle in 1857. South African Thesium was last revised by Hill almost a century ago. Since Hill's revision, the number of collections have grown, and 49 new species have been described. Currently, no comprehensive Thesium taxonomic key exists, and species delimitation remains difficult due to a high variation in character states, rendering the genus in need of major revision. Within southern Africa, ca. 103 species occur in the Greater Cape Floristic Region (GCFR), of which about 72 are regional endemics. The GCFR Thesium, including ecologicalspecialists and generalists, offers an appropriate system for evaluating both the correlates of range extent, specialisation and the relative extinction risks associated with both ecological strategies. Here, it is predicted that a combination of edaphic, elevation and climate variables influence the geographic range of Thesium in the GCFR. Recent phylogenetic hypotheses revealed that Thesium is paraphyletic with respect to Austroamericium, Chrysothesium, Kunkeliella and Thesidium, suggesting the need for generic realignment. In addition, existing subgeneric and sectional classifications of this large genus lack a phylogenetic basis, thus compromising their predictive value. Using an expanded taxon sampling and a combination of nuclear (ITS) and chloroplast (matK, rpl32- trnL and trnL-F) DNA sequence data, chapter two re-assesses the phylogenetic relationships of Thesium and uses these as the basis of a new subgeneric classification of the genus. The phylogeny obtained confirms the need to place the four segregate genera into synonymy, resulting in a monophyletic Thesium. In addition, it resolves five, well-supported major clades within Thesiumwhich I recognize as subgenera. The South African endemic subgenus Hagnothesium is sister to the Eurasian subgenus Thesium (including Thesium, Kunkeliella and Mauritanica). The subgenus Psilothesium, occurring in tropical South America (formerly genus Austroamericium) and tropical Africa, is sister to the rest of the subgenera, which are all confined to South Africa. Within the latter, the subgenus Discothesium consists of subtropical and temperate species, whereas subgenus Frisea, comprising previously recognized sections Annulata, Barbata Frisea, Imberbia and Penicillata, is restricted to the GCFR. To facilitate identification of subgenera, I present identification keys, assigned species, provide brief diagnoses, identified ancestral morphological characters and, supply distribution and ecological data. Thesium subgenus Hagnothesium is endemic to the GCFR. In the past, there has been a propensity in revisionarywork ofthe subgenus Hagnothesium to split taxa into distinctspecies or vice-versa. Consequently, 15 different names exist although only six are accepted formally. Following recent molecular phylogenetic studies, the monophyly of the subgenus Hagnothesium is now well-established, but the circumscription of species within the section remains problematic given the complicated nomenclatural history which has added further confusion. Chapter three presents a revision of subgenus Hagnothesium using a total evidence approach to propose a modern taxonomy. I studied both herbarium collections and plants in their natural populations to circumscribe species boundaries, geographical ranges and estimates of their conservation status. Species of the subgenus Hagnothesium are dioecious, generally having four- merous, campanulate flowers, spikes borne in bract axils and arranged along the length of branchlets, with valvate perianth lobes and a short to absent hypanthial tube. The following eight species were recognized, of which one is here described as new: T. fragile L.f., T. fruticulosum (A.W.Hill) J.C.Manning & F.Forest, T. hirtum (Sond.) Zhigila, Verboom & Muasya comb. nov., T. leptostachyum A.DC., T. longicaule Zhigila, Verboom & Muasya nom. nov., T. microcarpum A.DC., T. minus (A.W.Hill)J.C.Manning & F.Forest and T. quartzicolum Zhigila, Verboom & Muasya sp. nov. I provide updated taxonomic keys, species descriptions, illustrations, distribution maps, new combinations, synonyms, and notes on the red list status for each species. In addition, six new species of Thesium endemic to the GCFR (but not included in subgenus Hagnothesium) are described and illustrated in chapter four. These are: Thesium aspermontanum Zhigila, Verboom & Muasya sp. nov., T. dmmagiae Zhigila, Verboom & Muasya sp. nov., T. neoprostratum Zhigila, Verboom & Muasya sp. nov., T. nigroperianthum Zhigila, Verboom & Muasya sp. nov., T. rhizomatum Zhigila, Verboom & Muasya sp. nov., and T. stirtonii sp. nov. Also, Thesium assimile var. pallidum is elevated to species rank as T. sawae Zhigila, Verboom & Muasya stat. nov. Morphological and ecological differences between species, along with their putative affinities, preliminary conservation status, phenology, etymology and distributional maps are presented. Narrow-ranged species are expected to be more at greater risk of extinction than generalists due to climate change. Such risk is greatest in biodiversity hotspots such as the GCFR, which house both ecological specialists and generalists. It was hypothesized that range size, ecological specialization and consequent climatically-modulated extinction-risk are all phylogenetic structured, such that climate change will precipitate a disproportionate loss of phylogenetic diversity. Past and future species distribution ranges were developed using MaxEnt models based on present-day occurrences and environmental conditions. There was a strong positive correlation between the ecological niche breadth of species, as determined by large-scale environmental variables, and their range extents. One hundred and one Thesium species were modelled, of which 71 species (83%) were predicted to have had broad range sizes during the Last Glacial Maxima, and 27 species (17%) recorded range contractions historically to the present. Similarly, 45 species (44%) will potentially expand their ranges, while 51 species (50%) are predicted to reduce their ranges in the future. Of the 65 species currently ranked as Least Concern or Data Deficient in the South African Red list, 24 species will likely shift into higher extinction risk categories. Interestingly, five ecological specialists (5%), although having experienced a range reduction from the LGM to the present, are predicted to persist in the face of future climate change. However, the range extent, ecological specialisation and extinction risk are phylogenetically random and therefore should have a negligible impact on the phylogenetic diversity of the GCFR Thesium. Overall, this study confirms the monophyly of the genus Thesium and sets its infrageneric classification scheme in place. The context of this classification framework allows the systematic revision of the genus, one clade at a time. Towards this goal, I revised the Hagnothesium clade and additionally described six new species from other clades. The climate, elevation and soil variables influence the distribution range and specialism of GCFR Thesium clades. However, ecological specialism of species and extinction risks were predicted to be phylogenetically random.